2022
DOI: 10.1177/14614448221089604
|View full text |Cite
|
Sign up to set email alerts
|

In the eye of the beholder: A viewer-defined conception of online visual creativity

Abstract: Despite substantial interest in developing theoretical models and technology for creativity enhancement, existing creativity research across various fields lacks a user-centered definition of creativity that can be operationalized in today’s digital spaces. To address this, we conducted a mixed-methods longitudinal research on a study website mirroring content from Bēhance, a popular online platform for creatives. Specifically, we examined how content creators and consumers explored and reflected on online cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…In previous research (Herman & Hwang, 2022), I found that creative professionals (but not laypeople) fixated on evidence of artistic process when making creative judgments in algorithmic environments. This runs counter to previous creativity research, which discounts the role of process information in creative judgments.…”
Section: Background and Related Workmentioning
confidence: 90%
“…In previous research (Herman & Hwang, 2022), I found that creative professionals (but not laypeople) fixated on evidence of artistic process when making creative judgments in algorithmic environments. This runs counter to previous creativity research, which discounts the role of process information in creative judgments.…”
Section: Background and Related Workmentioning
confidence: 90%